STRATEGI BANDUNG SEBAGAI KOTA KREATIF DALAM UNESCO CREATIVE CITIES NETWORK (UCCN) - Sari, Mira Nofrika; Iskandar, Irwan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This research discusses the strategy of the Bandung City Government in making Bandung City as a UNESCO Creative City. Bandung is one of three cities in Indonesia that was included in the UNESCO Creative Cities Network (UCCN) in 2015. Currently, the city has become a joint discussion in international meetings. The important role of cities in promoting community-focused sustainable development and respecting for human rights is specifically recognized in the 2030 Agenda.          This qualitative study questions the strategy used by the Regional Government (Pemda) in following the international development agenda "Creative City (Creative City)". To answer this phenomenon, data is needed from books, journals, news, direct interviews with Bandung focal points for UNESCO as well as official documents from the Bandung City Government. The perspective and theory of Neoliberalism and the concept of the Creative City are used by researchers to analyze data and obtain research results.          Research shows that Bandung is one of the cities that apply the concept of Creative City (Creative City) to city development. Bandung uses the Pentahelix model which is a collaboration of academics, entrepreneurs, communities, and the media. The government and related parties collaborate to bring creative nuances to life in Bandung, because the government cannot work alone. Before carrying out the process of submitting a Creative City to UNESCO, the Mayor of Bandung appointed a dossier team. The Bandung dossier team first identified the basis for being a Creative City, then invited city stakeholders, searched and collected data on the potential / superiority of the city and analyzed it in a joint study. Since starting in 2012, the research has identified “Design” as a sub-sector that represents Bandung as a whole. The People-Place-Ideas formula was compiled to strengthen the narrative in the Bandung application when registering UNESCO Creative Cities. The submission process to UNESCO in 2012-2014 was carried out with a top-down system, namely through the central government. At that time, Bandung had not been selected as a UNESCO Network Creative City. In 2015, UNESCO changed the rule that City Governments can directly submit applications without going through the Central Government. So, in December 2015, Bandung was included in the UCCN City of Design according to the Decree of UNESCO Director-General Ref. Nr. DG/4/12/10370.  Keywords: Strategy, Bandung, Creative City, UCCN